2022
DOI: 10.1186/s12943-022-01529-5
|View full text |Cite|
|
Sign up to set email alerts
|

Circ-ZEB1 promotes PIK3CA expression by silencing miR-199a-3p and affects the proliferation and apoptosis of hepatocellular carcinoma

Abstract: Background Although the prognostic outcomes of liver cancer (LC) cases have improved with the advancement in diagnostic technology and treatment methods, the transferability and recurrence of HCC and the 5-year and 10-year survival rates of patients have remained unsatisfactory. As a result, there is a need for more accurate diagnostic indicators that can detect liver cancer early, effectively improving the prognosis of patients. Whole-genome sequencing (WGS) revealed that circ-ZEB1 and PIK3CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…Studies have shown that circRNAs might have a base sequence that binds to miRNAs, thereby act as a ceRNA to competitively bind to miRNAs, relieving the inhibitory effect of the miRNAs on their target genes, which then affects the occurrence and development of tumors [ 53 ]. Circ-ZEB1 promotes phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) expression by sponging miR-199a-3p, which affects the proliferation and apoptosis of hepatocellular carcinoma [ 54 ]. Our previous experiments found that hsa_circ_0021727 could act as a sponge for miR-23b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that circRNAs might have a base sequence that binds to miRNAs, thereby act as a ceRNA to competitively bind to miRNAs, relieving the inhibitory effect of the miRNAs on their target genes, which then affects the occurrence and development of tumors [ 53 ]. Circ-ZEB1 promotes phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) expression by sponging miR-199a-3p, which affects the proliferation and apoptosis of hepatocellular carcinoma [ 54 ]. Our previous experiments found that hsa_circ_0021727 could act as a sponge for miR-23b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…For example, upregulated circ-AKT1 could promote its parental gene AKT1 (v-akt murine thymoma viral oncogene homolog 1) expression by acting as miR-942-5p molecular sponge to suppress ovarian cancer tumor cells proliferation and migration ( 20 ). The apoptosis and cell cycle of tumor cell played important roles in tumor growth ( 62 ), recent studies had found that circFBLIM1 could function as a ceRNA to upregulate host gene FBLIM1 expression through sponging miR-346 and thus exert inhibitory effect in tumor cells apoptosis in hepatocellular cancer; circ-MAPK4 silencing had also been confirmed to downregulate its parental gene expression through ceRNA mechanism, resulting in upregulated phosphorylation level of P38/MAPK (mitogen-activated protein kinase) in glioma tumor cells and promoting tumor cells apoptosis ( 21 , 22 ). In addition, circ-VANGL1 knockdown was also found to prevent tumor cell cycle progression, resulting in more cells blocked at the G0/G1 stage ( 23 ).…”
Section: The Role and Molecular Mechanisms Of Circrnas Regulating Par...mentioning
confidence: 99%
“…To preliminarily analyze the molecular mechanisms by which dysregulated circRNAs could engage in keloid formation, we focused on ceRNA networks, where circRNAs can sponge miRNAs to regulate the expression of genes that is key to the pathogenesis of cancer or keloids [5,10]. By means of ENCORI databases, we found 251 miRNAs, each of which was predicted to bind with both one DEC and one DEG.…”
Section: Construction Of the Cerna Networkmentioning
confidence: 99%